2019
DOI: 10.1126/sciimmunol.aaw0336
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps drive inflammatory pathogenesis in malaria

Abstract: Neutrophils are essential innate immune cells that extrude chromatin in the form of neutrophil extracellular traps (NETs) when they die. This form of cell death has potent immunostimulatory activity. We show that heme-induced NETs are essential for malaria pathogenesis. Using patient samples and a mouse model, we define two mechanisms of NET-mediated inflammation of the vasculature: activation of emergency granulopoiesis via granulocyte colony-stimulating factor production and induction of the endothelial cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
167
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(180 citation statements)
references
References 97 publications
12
167
1
Order By: Relevance
“…We also observed an increase in the percentage of neutrophils among white blood cells and in the expression of neutrophil-specific genes in P. vivax infections, regardless of STH co-infection, confirming previous evidence that neutrophil activation is an important response to malaria (Aitken et al 2018). Indeed, a strong neutrophil response with the formation of extracellular traps is observed in acute P. falciparum patients (Knackstedt et al 2019). However, a previous study (Vallejo et al 2018) described a decrease in neutrophils and neutrophil specific genes in P. vivax infections, but this was only observed in first-time infections, possibly accounting for the differences with our results.…”
Section: Discussioncontrasting
confidence: 84%
“…We also observed an increase in the percentage of neutrophils among white blood cells and in the expression of neutrophil-specific genes in P. vivax infections, regardless of STH co-infection, confirming previous evidence that neutrophil activation is an important response to malaria (Aitken et al 2018). Indeed, a strong neutrophil response with the formation of extracellular traps is observed in acute P. falciparum patients (Knackstedt et al 2019). However, a previous study (Vallejo et al 2018) described a decrease in neutrophils and neutrophil specific genes in P. vivax infections, but this was only observed in first-time infections, possibly accounting for the differences with our results.…”
Section: Discussioncontrasting
confidence: 84%
“…NETs were found in zones adjacent to the nematode cuticle, whereas nodules derived from patients treated with the anti-Wolbachia drugs, doxycycline + ivermectin were depleted for Wolbachia and lacked NETs 65 . More recently it was reported that NETs would drive inflammation in malaria by releasing soluble NET components to facilitate parasite sequestration and tissue destruction, and inhibition of NETs as a treatment strategy in vascular infections was recommended 16 .…”
Section: Nets In Viral Fungal and Parasitic Infectionsmentioning
confidence: 99%
“…In addition to neutrophils, other granulocyte types can also form extracellular DNA traps, such as eosinophils (eosinophil extracellular traps, EETs) 9,10 and basophils (basophil extracellular traps, BETs) 11 . Over the last decade, a number of stimuli, microbial and noninfectious stimuli, able to induce extracellular trap formation have been identified [12][13][14][15][16] . It should be noted that there is an ongoing scientific dispute whether NET formation requires cell death or not [17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to contributing to the protection, activation of immune cells, when dysregulated, also promote disease pathogenesis. While neutrophils can mediate parasite killing when activated [19], they also release molecules such as proteases or neutrophil extracellular traps (NETs), which can also be very destructive to host tissues [20,21]. Pro-inflammatory mediators, such as IFN-γ and tumor necrosis factor (TNF), that support parasite killing and clearance can cause uncontrolled inflammation and lead to the sequestration of infected erythrocytes.…”
Section: Introductionmentioning
confidence: 99%